2021
DOI: 10.1155/2021/5588629
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Lobe Segmentation in CT Images Based on Lung Anatomy Knowledge

Abstract: In computed tomography (CT) images, pulmonary lobe segmentation is an arduous task due to its complex structures. To remedy the problem, we introduce a new framework based on lung anatomy knowledge for lung lobe segmentation. Firstly, the priori knowledge of lung anatomy is used to identify the fissure region of interest. Then, an oriented derivative of stick filter is applied to isolate plate-like structures from clutters for lobar fissure verification. Finally, a surface fitting model is employed to complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
(100 reference statements)
0
8
0
Order By: Relevance
“…Peng et al identified the fissure region of interest using lung anatomy prior knowledge and then isolated the plate-like structures from clutters utilizing an oriented derivative of stick filter for lobar fissure verification. Finally, to segment lung lobes, they completed the incomplete fissure surface employing a surface fitting model [ 66 ]. Qi et al noted that one reason for incomplete localization regions was neglecting the anatomical region relationships within each image and the inter-image relationships [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peng et al identified the fissure region of interest using lung anatomy prior knowledge and then isolated the plate-like structures from clutters utilizing an oriented derivative of stick filter for lobar fissure verification. Finally, to segment lung lobes, they completed the incomplete fissure surface employing a surface fitting model [ 66 ]. Qi et al noted that one reason for incomplete localization regions was neglecting the anatomical region relationships within each image and the inter-image relationships [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Existing work like Peng et al heavily depends on other tasks like airway segmentation. However, the segmentation is an arduous task as it is highly sensitive to the image quality [ 66 ]. They segmented pulmonary fissures using lung anatomy knowledge, which is time-consuming.…”
Section: Discussionmentioning
confidence: 99%
“…The human lungs are naturally divided into five separate functional compartments called lobes. The physical boundaries between lung lobes are known as lobar fissures 1 . Anatomically, the left lung is subdivided into two lobes (upper and lower lobes), whereas the right lung is subdivided into three lobes (upper, middle, and lower lobes), 2 as described in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional methods achieve the purpose of different semantic segmentation tasks by extracting features of the target objects (10)(11)(12), but the segmentation performance was not good enough. To overcome the problem, various deep learning frameworks have been proposed to effectively segment the target objects (13).…”
Section: Introductionmentioning
confidence: 99%